Convergent, Discriminant, and Incremental Validities of Person–Environment Fit Scale for Creativity in Predicting Innovative Behavior. (4th December 2018) - Duan, Wenjie; Li, Yumei
Abstract: This study examined the validity of a 14‐item two‐factor person–environment fit scale for creativity (PEFSC) to measure the personal and environmental components of creativity. A sample of 2, 475 participants completed the PEFSC for evaluating the factor structure. For convergent, discriminant, and incremental validities, a subsample ( N = 362) completed the creative self‐efficacy scale, support for innovation subscale of the team climate inventory, and innovative behavior measure. Results indicated the two‐factor correlated model showed a better goodness of fit than the one‐factor model. Measurement invariance of PEFSC was observed across different genders and educational groups. Internal consistency reliabilities were satisfactory (α ≥ .87). The personal dimension indicated stronger associations with creative self‐efficacy than with support for innovation, whereas the environmental dimension was related more closely to support for innovation than to creative self‐efficacy. Incremental validity was confirmed by significant and additional explanations from PEFSC in predicting innovative behavior. These results consolidated the application of person–environment fit theoretical framework in creativity research.